CLIPPINGS AND ABBREVIATIONS IN ENGLISH WORD-FORMATION - Khaydarova Nigora; Makhamadaliyeva Feruza (TADQIQOTLAR, 2025)
Abstract This  article  explores  two  important  processes  in  English  word-formation: clipping  and  abbreviation.  These  methods  are  part  of  linguistic  economy  and  are widely used in informal, academic, technical, and digital communication. The paper outlines the types, functions, structural patterns, and usage domains of clippings and abbreviations,  illustrating  how  they  contribute  to  the  dynamic  development  of vocabulary. Through comparison and examples, the study highlights their relevance in modern English and their increasing presence in global linguistic practices.